MEMBENTENGI KELUARGA TERHADAP BUDAYA KONSUMERISME DENGAN NILAI-NILAI KEHIDUPAN DALAM PENDIDIKAN KONSUMEN - Sri Wening (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2015)
Globalization era in free competition of goods and service is a challenge which can change any aspects of social life. The condition stimulates over buying behavior (materialistic behavior) and becomes threat because it tends to be consumptive behavior causing many human life values loose. The phenomena can fall out good manner norms, time accuracy, trusteeship, empathy, respect to the different ideas to other people. It is predicted that consumerism behavior happens because of the lack of knowledge, attitude, and skills in managing finance or intelligent finance in consumption. It happens because they are not prepared as early as possible to face market in respecting the value of money, either by family or school so that the consciousness of consumer is weak because of the low education. The main step to do is empowering to the consumer through constructing and educating to society. Constructing society can done through family and school. It needs to build the consciousness of consume well in the position as consumer although it is the right of the consumer as a form of consumer protection. Construction society through educating consumer, in which there is values of life, is expected to direct to the cultivating which build good consumer character in social life. The values of educating consumer is a part of education which is necessary to cultivate step by step and continue to grow and develop the consumer consciousness to be a good personal character to avoid consumerism culture.